Transcriptomic and metabolomic profiling reveals the drought tolerance mechanism of Illicium difengpi (Schisandraceae) - Zhang, Xiu-Jiao; Wu, Chao; Liu, Bao-Yu; Liang, Hui-Ling; Wang, Man-Lian; Li, Hong (Frontiers in Plant Science, 2024)
Illicium difengpi (Schisandraceae), an endangered medicinal plant endemic to karst areas, is highly tolerant to drought and thus can be used as an ideal material for investigating adaptive mechanism to drought stress. The understanding of the drought tolerance of I. difengpi, especially at the molecular level, is lacking. In the present study, we aimed to clarify the molecular mechanism underlying drought tolerance in endemic I. difengpi plant in karst regions. The response characteristics of transcripts and changes in metabolite abundance of I. difengpi subjected to drought and rehydration were analyzed, the genes and key metabolites responsive to drought and rehydration were screened, and some important biosynthetic and secondary metabolic pathways were identified. A total of 231,784 genes and 632 metabolites were obtained from transcriptome and metabolome analyses, and most of the physiological metabolism in drought-treated I. difengpi plants recovered after rehydration. There were more upregulated genes than downregulated genes under drought and rehydration treatments, and rehydration treatment induced stable expression of 65.25% of genes, indicating that rehydration alleviated drought stress to some extent. Drought and rehydration treatment generated flavonoids, phenolic acids, flavonols, amino acids and their derivatives, as well as metabolites such as saccharides and alcohols in the leaves of I. difengpi plants, which alleviated the injury caused by excessive reactive oxygen species. The integration of transcriptome and metabolome analyses showed that, under drought stress, I. difengpi increased glutathione, flavonoids, polyamines, soluble sugars and amino acids, contributing to cell osmotic potential and antioxidant activity. The results show that the high drought tolerance and recovery after rehydration are the reasons for the normal growth of I. difengpi in karst mountain areas.